SPE Latin American and Caribbean Petroleum Engineering Conference 2015
DOI: 10.2118/177174-ms
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Polymer Assisted WAG for Mobility Control in the Highly Heterogeneous North Burbank Unit in Oklahoma, Using Anthropogenic CO2

Abstract: This work investigates the use of polymers during CO 2 WAG using a physical model. Coreflooding experiments were conducted to compare polymer assisted WAG, conventional WAG, continuous CO 2 flooding, and polymer flooding. The effect of miscibility in the CO 2 -oil interface was evaluated from coreflooding at two different pressures, above and below the MMP of 1563 psig The MMP was experimentally determined using a fast version of the slim tube procedure with a shorter column. The influence of reservoir heterog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The 13 coreflood experiments in light oil (viscosity = 3.21 cP) were conducted to compare the performance of PAG-CO 2 with other methods. 7 For homogeneous cores, PAG did not show improvement in oil recovery from WAG under immiscible conditions and even worsened oil recovery under miscible conditions as polymer shielded more residual oil. For heterogeneous cores, PAG yielded similar results as WAG because the better mobility control by polymer possibly reduced the fingering dispersion.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…The 13 coreflood experiments in light oil (viscosity = 3.21 cP) were conducted to compare the performance of PAG-CO 2 with other methods. 7 For homogeneous cores, PAG did not show improvement in oil recovery from WAG under immiscible conditions and even worsened oil recovery under miscible conditions as polymer shielded more residual oil. For heterogeneous cores, PAG yielded similar results as WAG because the better mobility control by polymer possibly reduced the fingering dispersion.…”
Section: Introductionmentioning
confidence: 89%
“…The superior performance of PGAW over WAG suggested that more favorable mobility control improved macroscopic displacement efficiency. The 13 coreflood experiments in light oil (viscosity = 3.21 cP) were conducted to compare the performance of PAG-CO 2 with other methods . For homogeneous cores, PAG did not show improvement in oil recovery from WAG under immiscible conditions and even worsened oil recovery under miscible conditions as polymer shielded more residual oil.…”
Section: Introductionmentioning
confidence: 99%
“…Few coreflood experiments on sandstone cores have been conducted to demonstrate the efficacy of PAG injection, but these experiments either used model crude oil or lacked comprehensive discussion on the displacement mode of crude oil by CO 2 during PAG injection. , A micromodel study was conducted to explain the recovery mechanism of miscible PAG for 0.5 cP oil using SAV55 polymer . Furthermore, Tovar et al studied the effect of heterogeneity on miscible or immiscible displacement of oil by PAG injection in sandstone core, and their findings indicated that a certain level of heterogeneity is necessary for PAG injection to yield beneficial results. It has been observed that most of the studies focused on analyzing individual parameters to explain the additional recovery achieved through PAG injection, without fully integrating the mechanisms or optimizing various parameters such as MMP, IFT reduction, viscosity reduction, CO 2 solubility and crude oil swelling factor, and injection rate of fluids.…”
Section: Introductionmentioning
confidence: 99%